Valiant, vital and virtuous - A time-snap review - Itkonen, Matti (European Journal of Multidisciplinary Studies, 2020)
A time-snap review – moments captured pictorially – means the creation of multi-layered observation. The enquiring gaze then extends beyond the present moment: to its existential roots. However, it is not a question of presenting an historical list, a collection of topics of various types and periods. Of course, understanding the present also requires knowledge of the people and events of the past. In this way it also becomes possible to study the recurring nature of existence. Can war-related travel also count as cultural travel? Is it possible to talk about war tourism? Presumably, in many countries the answer to this will be positive. It relates to the history of ideas and also to national sentiment. This kind of cultural education may be indoctrinating in character, with the goal of insinuating into people’s minds the concept of the incomparable excellence of their own nationality. The spirit of the 2010s contains shades of indoctrination. Fortunately, alongside this struggle to impress, education for democracy is also present. Photographs and poetry are powerful media, helping us to create a nostalgia for being. Then, too, a longing for the past is awakened. It is here that a philosophy of yearning or wistfulness is needed, providing an exploratory tool for analyzing the nature of the individual and the community. Modernity needs philosophical poet-travellers. They are adept at loving the wisdom of travel.